Mengapa Pengguna Narkoba pada Remaja Akhir Relapse? - Evi Afifah Hurriyati (Humaniora, 2010)
This research is to acknowledge causes why drug users in late adolescent, who had followed drug recovery program in drug rehabilitation centre, are relapsing at the time they came back to subject environment. This research’s background is supported with the increasing numbers of drug addictive users in Indonesia, especially in adolescent. The result of this research showed an uncondusive situation, such as conflict with parents (father) when they got back to house environment, causes they are coping maladaptive, i.e. relapse. Conflict with father causes adolescent has negative perception towards social support from the father, and it effects their religious orientation and locus of control. For future research, it is suggested to do quantitative research so it can be gained measurable result statistically.